A Medieval/Early Modern Alpine Population from Zweisimmen, Switzerland: A Comparative Study of Anthropology and Palaeopathology. (6th September 2017) - Somers, J.; Cooper, C.; Alterauge, A.; Lösch, S.
Abstract: To date, anthropological comparative studies from Switzerland are rare. Therefore, this research aims to make a comparison between the alpine individuals from Zweisimmen (ca. 14th–19th), and 17 other rural and urban populations from Switzerland all dating to the medieval and early modern period. An osteoarchaeological analysis was carried out on the rural population of Zweisimmen, consisting of 134 skeletons. For each individual, the arm position and orientation were observed in the field, while preservation, representation, sex, age, stature, trauma and pathologies were recorded in the laboratory. These results were compared with data from published and grey literature in order to gain a better understanding of chronological and regional patterns in Switzerland. A chronological development was observed in the orientation, arm position and use of a coffin, which suggests a change in burial practices and beliefs throughout time. The demographic profile represents a natural mortality; however, children and especially neonates are underrepresented in this sample. Some individuals were buried in groups, suggesting simultaneous burial during a period of increased mortality. The palaeopathological findings suggest that the living conditions in rural alpine Zweisimmen were similar to those of other contemporaneous populations, as well as those living in an urban setting. Copyright © 2017 John Wiley & Sons, Ltd.